Surface Modification of 2D Photocatalysts for Solar Energy Conversion - Feng, Chengyang; Wu, Zhi‐Peng; Huang, Kuo‐Wei; Ye, Jinhua; Zhang, Huabin (Advanced materials (Weinheim), 2022)
2D materials show many particular properties, such as high surface‐to‐volume ratio, high anisotropic degree, and adjustable chemical functionality. These unique properties in 2D materials have sparked immense interest due to their applications in photocatalytic systems, resulting in significantly enhanced light capture, charge‐transfer kinetics, and surface reaction. Herein, the research progress in 2D photocatalysts based on varied compositions and functions, followed by specific surface modification strategies, is introduced. Fundamental principles focusing on light harvesting, charge separation, and molecular adsorption/activation in the 2D‐material‐based photocatalytic system are systemically explored. The examples described here detail the use of 2D materials in various photocatalytic energy‐conversion systems, including water splitting, carbon dioxide reduction, nitrogen fixation, hydrogen peroxide production, and organic synthesis. Finally, by elaborating the challenges and possible solutions for developing these 2D materials, the review is expected to provide some inspiration for the future research of 2D materials used on efficient photocatalytic energy conversions. Although the research of 2D photocatalysts has made great progress in the past decades, there are still many challenges in understanding the deep relationship between the surface state and the reaction mechanism. The surface modification strategies and reaction mechanisms of 2D photocatalysts are reviewed, and some useful views are put forward for future research in this field.